2020
DOI: 10.3390/nu12092844
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Decoration of Glutenin during Heat Processing Could Alleviate the Resulting Allergic Reaction in Mice

Abstract: Background: It is widely believed that Maillard reactions could affect the sensitization of allergens. However, the mechanism of action of methylglyoxal (MGO) production in Maillard reactions in the sensitization variation of glutenin (a predominant allergen in wheat) during heat processing is still unclear. Methods: This research evaluated the effect of MGO on the immune response against glutenin in a mouse model. The resulting variations in conformation and corresponding digestibility of glutenin were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In this study we chose to establish a mouse model of glutenin for the following reasons: (i) it is unknown at present whether wheat glutenin has the intrinsic capacity to elicit IgE antibody responses and whether it can cause systemic anaphylaxis in the absence of exercise as a cofactor; (ii) it is unknown at present whether wheat glutenin skin exposure can clinically sensitize mice for systemic anaphylaxis; (iii) most of the previous mouse models of wheat hypersensitivity have used wheat gliadins for developing the models; (iv) there are only two previous mouse model studies, both of which used adjuvants to elicit IgE responses to glutenin [19,26]. Kozai et al, 2006, reported the first mouse model to elicit IgE antibody responses to wheat glutenin [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we chose to establish a mouse model of glutenin for the following reasons: (i) it is unknown at present whether wheat glutenin has the intrinsic capacity to elicit IgE antibody responses and whether it can cause systemic anaphylaxis in the absence of exercise as a cofactor; (ii) it is unknown at present whether wheat glutenin skin exposure can clinically sensitize mice for systemic anaphylaxis; (iii) most of the previous mouse models of wheat hypersensitivity have used wheat gliadins for developing the models; (iv) there are only two previous mouse model studies, both of which used adjuvants to elicit IgE responses to glutenin [19,26]. Kozai et al, 2006, reported the first mouse model to elicit IgE antibody responses to wheat glutenin [19].…”
Section: Discussionmentioning
confidence: 99%
“…Wheat gliadin has been used in most gluten allergy mouse model studies [20,22,24,25]. There are two mouse models reported for wheat glutenin hypersensitivity [19,26]. While these models are very useful with their own strengths and novelty, there are few major challenges that limit their applications, such as: (i) use of adjuvants to elicit sensitization to glutenin; (ii) exposure to glutenin via injections to elicit sensitization; and (iii) lack of robust quantitative readouts of systemic anaphylaxis (e.g., hypothermia shock response, and mediators).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a-DCs could interact with the side-chain groups of arginine (Arg) and lysine (Lys) residues. Among all of the a-DCs, MGO exists the most widely in heat-processed foods ( Kim et al, 2021 , Wang et al, 2020 , Zheng et al, 2022 , Zhuang et al, 2020 ). MGO in fats and oils is also formed by lipid degradation during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Methylglyoxal (MGO) has the highest reactivity as intermediate in the MR. The project of Wang et al aimed to determine the effect of MGO on the allergenicity of glutenin based on the BALB/c mouse model pre-sensitized to native glutenin, heated glutenin and MGO-glutenin, in order [ 18 ]. The digestibility and changes in the structure of glutenin and gut microflora in mice were analysed to elucidate the detailed mechanism by which the potential for allergic reaction is reduced as a result of MGO decoration.…”
mentioning
confidence: 99%